Butaphosphan and Cyanocobalamin Supplementation in Semen Extender on Chilled Boar Sperm Quality and Life Span - Suwimonteerabutr, J.; Chumsri, S.; Tummaruk, P.; Nuntapaitoon, Morakot (Frontiers in Veterinary Science, 2020)
The objective of the present study was to determine the effect of butaphosphan and cyanocobalamin supplementation in semen extender on chilled boar sperm quality and life span. A total of 35 ejaculates of boar semen were included. The semen was diluted with Beltsville thawing solution extender supplemented with different concentrations of butaphosphan and cyanocobalamin [0 (control), 0.1, 0.2, 0.3, 0.4, and 0.5%] in the diluted semen. The semen samples were evaluated using a computer-assisted sperm analysis system to determine sperm motility and sperm kinetic parameters (i.e., the curvilinear velocity, VCL; straight line velocity, VSL; average path velocity, VAP; linearity, LIN; straightness, STR; amplitude of lateral head, ALH; wobble, WOB; and beat cross frequency, BCF). Additionally, sperm viability, acrosome integrity, mitochondrial activity, and plasma membrane integrity were evaluated after 4 (day 0), 72 (day 3), 120 (day 5), and 168 (day 7) h of storage using SYBR-14–ethidium homodimer-1 (EthD-1), EthD-1, JC-1, and the short hypo-osmotic swelling test, respectively. The analyses were carried out by using the general linear mixed model (MIXED) procedure of SAS. The statistical models for each data set included group, day after storage, and interaction between group and day after storage. The boar was included as a random effect. On day 0 after storage, progressive motility, VCL, VSL, VAP, and plasma membrane integrity of boar sperm in 0.3% of butaphosphan and cyanocobalamin supplementation were greater than those in the 0.4 and 0.5% groups (P < 0.05). On day 3 after storage, total motility and progressive motility, VCL, VSL, VAP, LIN, WOB, BCF, and plasma membrane integrity in 0.3% of butaphosphan and cyanocobalamin supplementation were significantly greater than those in the control group (P < 0.05). The total motility and progressive motility, VAP, and WOB in 0.3% of butaphosphan and cyanocobalamin supplementation were greater than those in the control group on day 5 after storage (P < 0.05). No effects of butaphosphan and cyanocobalamin supplementation on acrosome integrity and mitochondria activity were found on days 3, 5, and 7 after storage. However, the motility and progressive motility and the values for all sperm kinetic parameters except ALH in 0.3% of butaphosphan and cyanocobalamin supplementation were greater than those in the control group on day 7 after storage (P < 0.05). In conclusion, 0.3% of butaphosphan and cyanocobalamin supplementation in semen extender improved sperm motility, sperm activity, morphology, and life span in chilled boar sperm.